Real-World Outcome Analysis of Patients With Stage IV NSCLC Treated With Tyrosine Kinase and Immune Checkpoint Inhibitors - Ryo Ariyasu, MD; Sho Kakuto, MD; Keiki Miyadera, MD; Takahiro Akita, MD; Ayu Kiritani, MD; Ryosuke Tsugitomi, MD; Yoshiaki Amino, MD; Ken Uchibori, MD, PhD; Satoru Kitazono, MD, PhD; Noriko Yanagitani, MD, PhD; Makoto Nishio, MD, PhD (JTO Clinical and Research Reports, 2023)
Introduction: Only a few reports have determined whether recently advanced anticancer drugs, particularly next-generation tyrosine kinase inhibitors (TKIs) and immune checkpoint inhibitors (ICIs), prolong the survival of patients with NSCLC in the real world. Methods: To evaluate the association between recently advanced drugs and patient survival, survival data of 2078 patients with stage IV NSCLC from 1995 to 2022 were analyzed in the present study. The patients were classified into the following six groups in terms of the date of diagnosis: period A, 1995 to 1999; period B, 2000 to 2004; period C, 2005 to 2009; period D, 2010 to 2014; period E, 2015 to 2019; and period F, 2000 to 2022. They were further grouped in terms of EGFR mutation and ALK fusion. Results: The median overall survival (mOS) times were 8.9, 11.0, 13.6, 17.9, and 25.2 months in periods A to E, respectively, and the mOS time was not reached in period F. This time was significantly longer in period E than in period D (25.2 versus 17.9 mo, p < 0.005). Moreover, the mOS times of patients with EGFR mutation, those with ALK fusion, and those without both alterations were significantly longer in period E than in period D (46.0 versus 32.0 mo, p < 0.005; not reached versus 36.2 mo, p = 0.018; 14.6 versus 11.7 mo, p < 0.005). The history of treatment with next-generation TKIs and ICIs was found to be associated with overall survival. Conclusions: The survival of patients with NSCLC was improved from period D to period E, regardless of the presence of driver gene alteration. We found that next-generation TKIs and ICIs may be associated with improvements in overall survival.